Hebräischunterricht und Hebraistik in Deutschland und deutschsprachigen Ländern: Eine Bestandsaufnahme - Golinets, Viktor (Forum Exegese und Hochschuldidaktik: Verstehen von Anfang an, 2018)
The paper describes developments within Hebrew S tudies in Germany with an outlook to other German-speaking countries. It reviews several research trends of the nineteenth and twentieth centuries and delineates the current s tate. Traditionally, Hebrew S tudies in Germany deal with Biblical Hebrew, and academic teaching of this language takes place at theological ins titutions. This chronological and ins titutional focus res tricts the research field, whereby later s tages of linguis tic development become neglected. Even today, while Modern Hebrew is a flourishing language, its teaching is being conducted at a very small number of locations. Currently, there is only one chair in Modern Hebrew S tudies in Germany and German speaking countries, and that is merely of an Assis tant Professor range. Present growth of Israel and Near Eas tern S tudies in Germany and continuing interest in Modern Hebrew demands es tablishing of Hebrew S tudies at more locations. The research and teaching should cover all chronological and geographical layers of Hebrew as well as apply sundry linguis tic methods.